Facilitating Layered Oxide Cathodes Based on Orbital Hybridization for Sodium‐Ion Batteries: Marvelous Air Stability, Controllable High Voltage, and Anion Redox Chemistry - Jia, Xin‐Bei; Wang, Jingqiang; Liu, Yi‐Feng; Zhu, Yan‐Fang; Li, Jia‐Yang; Li, Yan‐Jiang; Chou, Shu‐Lei; Xiao, Yao (Advanced materials (Weinheim), 2024)
Layered oxides have become the research focus of cathode materials for sodium‐ion batteries (SIBs) due to the low cost, simple synthesis process, and high specific capacity. However, the poor air stability, unstable phase structure under high voltage, and slow anionic redox kinetics hinder their commercial application. In recent years, the concept of manipulating orbital hybridization has been proposed to simultaneously regulate the microelectronic structure and modify the surface chemistry environment intrinsically. In this review, the hybridization modes between atoms in 3d/4d transition metal (TM) orbitals and O 2p orbitals near the region of the Fermi energy level (EF) are summarized based on orbital hybridization theory and first‐principles calculations as well as various sophisticated characterizations. Furthermore, the underlying mechanisms are explored from macro‐scale to micro‐scale, including enhancing air stability, modulating high working voltage, and stabilizing anionic redox chemistry. Meanwhile, the origin, formation conditions, and different types of orbital hybridization, as well as its application in layered oxide cathodes are presented, which provide insights into the design and preparation of cathode materials. Ultimately, the main challenges in the development of orbital hybridization and its potential for the production application are also discussed, pointing out the route for high‐performance practical sodium layered oxide cathodes. Based on orbital hybridization theory, the challenges of layered oxide cathodes in terms of air stability, high voltage, anion redox chemistry, and improving the intrinsic characteristics through interactions between the 3d/4d transition metal and the O 2p atomic orbitals are summarized. This strategy of modulating orbitals hybridization will promote the development of sodium layered oxide cathodes and its commercialization process.